Colorimetric Detection by Gold Nanoparticle DNA Probes for Miltenberger Series (GP.Mur, GP.Hop, and GP.Bun) Identification. Issue 6 (13th April 2016) - Vongsakulyanon, Apirom; Pipatpanukul, Chinnawut; Kitpoka, Pimpun; Kunakorn, Mongkol; Srikhirin, Toemsak
Abstract : Background: Miltenberger (Mi) series are the collective glycophorin hybrids in the MNS blood group system. Mi series are composed of several subtypes, for examples, GP.Mur, GP.Hop, and GP.Bun. The incompatibility of Mi series blood transfusion poses the risk of hemolysis. Due to the lack of standard antibodies for Mi series blood typing, colorimetric gold nanoparticle (AuNP) DNA probes were therefore explored for Mi series identification. Methods: AuNPs were synthesized and conjugated to an RvB (test) probe and an RvA2 (control) probe. Each of the AuNP DNA probes was tested against the amplified products of Mi(+) (GP.Mur/Hop/Bun), Mi(–), and the blank (no amplified product). The change in color was observed by visual inspection and UV‐Vis spectroscopy. Results: The amplified product of the Mi(+) sample retained the color on both probes (test+/control+). The amplified product of the Mi(–) sample retained the color only on the control probe (test–/control+) and the amplified product of the blank turned clear on both probes (test–/control–). The results by optical density absorbance measurement were concordant with the results by visual inspection. Both probes were validated with the amplified products of the ten Mi(+) and ten Mi(–) samples. All of the samples were correctly identified. Conclusion: AuNP DNA probes (RvB and RvA2) could be applied to distinguish the amplified products of Mi(+), Mi(–), and the blank by visual inspection and/or OD absorbance measurement.